Production and quality of yoghurt in dairy industry Zenica - Sonja Bijeljac; Hajrudin Skender; Zlatan Sarić (Mljekarstvo)
Nowadays, when consumers are more aware of influence of feed on the health, yoghurt gains higher importance. Therefore, its consumption raises everyday. It is perfect fermented milk and source of high valuable nutrients. Yoghurt is one of the most prominent products in assortment of Dairy Industry Zenica. Manufacture of yoghurt was monitored during 10-month period i.e. from June 2002 to March 2003. Productions from 233 producing days were included in determination. Special attention was paid to quality of raw material for yoghurt manufacture. The quality of raw milk for yoghurt production was high. Average relative density was 1,030. Acidity varied from 6.11 to 6.64oSH, with mean value of 6.28oSH. Evaporating of milk and addition of skim milk dry powder were used for dry solids adjustment required for good quality yoghurtmanufacture. Milk for yoghurt manufacture, had relative density from 1.035 to 1.036 with average value of 1.035. Acidity ranged from 7.07 to 7.59oSH. Average acidity was 7.30oSH. Fat content was in range from 1.94 to 2.00% and 1.98% in average. Yoghurt starter culture showed high acidic activity, as indicated in its acidity value before inoculation of yoghurt milk. Mean value of acidity of starter culture was 40.36oSH with variations from 38.05 to 42.64oSH. The acidity of final product varied from 37.36 to 38.81oSH or 38.26oSH in average. The acidity of yoghurt in Dairy Industry Zenica was adjusted to be somewhat lower than usual in order to keep high quality of products during distribution and consuming chain.